Peningkatan Minat Belajar Bahasa Indonesia melalui Aplikasi Wordwall: Studi Kasus Kelas IX-1 SMP Negeri 5 Padangsidimpuan - Lubis, Anita Angraini (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2023)
This study investigates the effectiveness of Wordwall, a web-based learning platform, in boosting understanding and interest in Indonesian language learning for junior high school level IX students. The study implemented a mixed-methods approach. Data was collected through observations of teaching and learning patterns, interviews with students and teachers, and pre- and post-intervention tests to assess student learning outcomes. Data analysis involved reduction, presentation, and drawing conclusions. The results showed that using Wordwall led to a significant increase in student learning outcomes and a noticeable improvement in both their understanding and interest in Indonesian language learning. This suggests that Wordwall, which allows convenient access to learning materials through student devices anytime and anywhere, can be an effective tool for enhancing teacher-student engagement and improving student achievement in Indonesian language education.